(3Gdbhd GdJGe aj BOGH ONhd GdMeGes - (3TgGH GdOjf CHh GdYHGS CMeO Hf YeGO GdOjf GdCabgSj,J (B808 (3g` s ((3eMeO Hf CMeO Hf YHO Gddg Hf CMeO Hf SdjeGf Hf ESeGYjd GdYHGSi s)
(3ChdgG (B:s
(3GdMeO ddg GdHQ GdcQje CPcQ ajg CHhGHkG JJYdb HGdOGNd TQYjI , hehGfY JJYdb HGdHOf WHjI , djchf OGNd GdMeGe Ydi HUjQI , ajJYGWi eG jJaYg hjLJfH eG jaUO Hg HOfg hjVQg s
(3BNQgG (B:s
(3Ke jCcdhf HYO Pdc eG jOaY GdUaQI GdJi JbYO ai GdQCS , hGddg CYde HGdUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B184 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCeHQhRjGfG (B(47) s
Keywords: (3GdWHs